2004
DOI: 10.1162/0898929042568479
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Syntactic Ambiguity in Sentence Comprehension for Low and High Span Readers

Abstract: Syntactically ambiguous sentences have been found to be difficult to process, in particular, for individuals with low working memory capacity. The current study used fMRI to investigate the neural basis of this effect in the processing of written sentences. Participants with high and low working memory capacity read sentences with either a short or long region of temporary syntactic ambiguity while being scanned. A distributed left-dominant network in the peri-sylvian region was identified to support sentence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 66 publications
6
73
0
1
Order By: Relevance
“…Interestingly, the sentence complexity and taskdemand conditions did not interact (i.e., the task effect was equally robust for SR and OR sentences). We note that this finding of no different localization of subject and object relative constructions in terms of L-IFC activation is in line with the current work of Fiebach et al (2004) and Wartenburger et al (2004) who investigated canonical and non canonical forms.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the sentence complexity and taskdemand conditions did not interact (i.e., the task effect was equally robust for SR and OR sentences). We note that this finding of no different localization of subject and object relative constructions in terms of L-IFC activation is in line with the current work of Fiebach et al (2004) and Wartenburger et al (2004) who investigated canonical and non canonical forms.…”
Section: Discussionsupporting
confidence: 92%
“…This may be related to the working memory component needed to maintain elements of the narrative in an active state during its production. Evidence consistent with a role for working memory during narrative production comes from superior performance (Singer & Ritchot, 1994) and greater frontal activation (Fiebach, Vos, & Friederici, 2004;Virtue, Haberman, Clancy, Parrish, & Jung Beeman, 2006) in subjects with higher working memory spans. Working memory in the service of complex sentence processing also is associated with dorsal inferior frontal activation (Cooke et al, 2006).…”
Section: Left Inferior Frontal Support For Working Memorymentioning
confidence: 89%
“…Our results tie in with those from a study by Chan and colleagues (2004), who used a word-generation paradigm, and reported that isolated, lexically ambiguous words (compared to unambiguous words) elicited relative activation decreases in the LIFG, but relative increases in medial frontal cortex. In contrast, both syntactic and lexical ambiguity have been reported to enhance activity in LIFG regions when examined with sentence comprehension paradigms (e.g., Fiebach et al, 2004;Mason et al, 2003;Rodd et al, 2005). However, lexical ambiguity may also invoke semantic implausibility depending on the meaning that is pursued (e.g., "there was thyme/time and sage…", Rodd et al, 2005), and syntactically ambiguous sentences often contain unusual constructions (e.g., "The experienced soldiers warned about the dangers before the midnight raid.…”
Section: Referential Ambiguity and Medial Prefrontal Regionsmentioning
confidence: 99%